2009
DOI: 10.1007/s11739-009-0297-5
|View full text |Cite
|
Sign up to set email alerts
|

The microcirculation as a diagnostic and therapeutic target in sepsis

Abstract: The microcirculation is defined as the smallest vessels where gas and nutrient exchange with tissues takes place. One of its primary functions is to ensure adequate oxygen delivery to meet the oxygen demands of tissue cells. Previous data from clinical and experimental studies and the recent development of new imaging modalities, such as Orthogonal Polarization Spectral videomicroscopy and Sidestream Dark Field imaging, have helped to identify the crucial role that microcirculation plays in sepsis. If not corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…We used CASP model, which appears (together with cecal ligation and puncture (CLP)) to be the best existing alternative for emulating human polymicrobial sepsis to date and could mimic the pathophysiologic consequences of sepsis (Hubbard et al, 2005;Traeger et al, in press). We found significant changes only in microcirculation; this observation agree with Dyson et al (Dyson et al, 2012), who suggested the uncoupling of macrovascular function and microvascular flow impairment during early sepsis, and that microcirculatory derangements may be present even in the absence of global hemodynamic deficiency (De Backer et al, 2010;Nencioni et al, 2009). This could be explained by various events occur at the microcirculatory, such as disturbed balance between vasoconstrictive and vasodilatory substances, microthrombi and, more frequently, plugs of leukocyte and erythrocyte.…”
Section: Discussionsupporting
confidence: 92%
“…We used CASP model, which appears (together with cecal ligation and puncture (CLP)) to be the best existing alternative for emulating human polymicrobial sepsis to date and could mimic the pathophysiologic consequences of sepsis (Hubbard et al, 2005;Traeger et al, in press). We found significant changes only in microcirculation; this observation agree with Dyson et al (Dyson et al, 2012), who suggested the uncoupling of macrovascular function and microvascular flow impairment during early sepsis, and that microcirculatory derangements may be present even in the absence of global hemodynamic deficiency (De Backer et al, 2010;Nencioni et al, 2009). This could be explained by various events occur at the microcirculatory, such as disturbed balance between vasoconstrictive and vasodilatory substances, microthrombi and, more frequently, plugs of leukocyte and erythrocyte.…”
Section: Discussionsupporting
confidence: 92%
“…In a septic shock model of peritonitis by cecal ligation and puncture in rats, Lam et al [42] used intravital videomicroscopy and showed that sepsis altered microvascular perfusion, with increased microcirculation flow heterogeneity and reduced functional capillary density. Therefore, microcirculation's dysfunction may appear as a major mechanism in the development of multiple organ failure [45]. Therefore, microcirculation's dysfunction may appear as a major mechanism in the development of multiple organ failure [45].…”
Section: The Inflammatory Endotheliummentioning
confidence: 99%
“…Sepsis is therefore responsible for an intense cellular activation; endothelial cells will amplify the inflammatory response by releasing proinflammatory cytokines, which contribute to spreading of microcirculatory injuries [45]. In a mouse endotoxemic shock model, Meziani et al [47] demonstrated that human serum albumin reduced endotoxemiainduced inflammation, by decreasing the up-regulation of I B , thus blunting the activation of NF-B.…”
Section: The Inflammatory Endotheliummentioning
confidence: 99%
“…Using OPS imaging we were the first to image the human brain microcirculation during surgery [21]. Since then, numerous studies have been undertaken in various clinical scenarios where cardiovascular function is at risk (for example, [1-3,7,8,10,11]).…”
Section: Brief History Of Clinical Imaging Of the Microcirculationmentioning
confidence: 99%